Persepsi Guru Terhadap Pembelajaran Daring Di Sekolah Dasar - Rusmiati; Nurmalina, Nurmalina (Jumper: Journal of Educational Multidisciplinary Research, 2022)
Online learning requires learning media that make it easier for students to understand the subject matter. Online learning carried out in elementary schools must have good cooperation between educators and parents of students. The purpose of this study was to find out how the teacher's perception and the obstacles faced in the implementation of online learning at the State Elementary School 8 Kebayakan Takengon. This research uses descriptive qualitative research, where data collection techniques use interview techniques. The subject of this research is the teacher of the State Elementary School 8 Kebayakan Takengon. The results of the study show that online learning for elementary school-aged children is used as additional learning, supporting learning, and substitute learning. The obstacles faced during online learning in the form of an unsupported internet network in the area where students live, the lack of mastery of technology by educators and students, and the limited means of online learning equipment in the form of not having an Android cellphone, laptop or computer. And the need for a high internet quota is an additional cost for parents of students